COMPLEMENTARY MEDICINE PRACTICES FOR PREGNANCY AND POSTPARTUM HEALTH: A STUDY AMONG MALAYSIAN WOMEN WHO GAVE BIRTH IN A TERTIARY CENTRE - Amirah MS; Farahiyah SK; Sugathan S; Ohn Mar S (Asian Journal of Medicine & Health Sciences, 2019)
Background: A systematic review reported a high prevalence of complementary and alternative medicine (CAM) practice during pregnancy. Earlier Malaysian studies related to it were based on Malay predominant populations. Objectives: The study objectives were to determine prevalence, types, aims, and associated factors of CAM use during pregnancy and the postnatal period among women who gave birth in a Malaysian tertiary hospital. Methods: A cross sectional study was conducted among women who were admitted to the postnatal wards of “Hospital Raja Permaisuri Bainun, Ipoh, Perak state, Malaysia” using a structured questionnaire, designed to collect data on the participants’ demography, details of CAM practice and their attitude towards its use. Results: The prevalence of CAM use among 134 respondents was 87.3%. The most commonly used method was naturopathy using abdominal hot stone application or massage as reported by 72% respondents. It was rated highly effective in improving circulation or recuperation by 90% of users. Herbal usage was reported by 36% and the commonest type was Indonesian traditional herbal medicine “Jamu”. The use of CAM was significantly low among Chinese respondents (P<0.001), respondents with no/primary level education background (P<0.05), unskilled workers (P<0.05) and low earners (P<0.005). Regression analysis indicated the chance of CAM usage was significantly less among Chinese women compared to Malays. (OR = 0.077 95% CI= 0.013-0.458) Conclusion: The prevalence of obstetric CAM use among the study population was high. Further studies are required to critically assess the commonest practice, naturopathy.